2015
DOI: 10.1111/cas.12592
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and therapeutic effect of styrene–maleic acid copolymer‐conjugated pirarubicin

Abstract: Previously, we prepared a pirarubicin (THP)-encapsulated micellar drug using styrene–maleic acid copolymer (SMA) as the drug carrier, in which active THP was non-covalently encapsulated. We have now developed covalently conjugated SMA-THP (SMA-THP conjugate) for further investigation toward clinical development, because covalently linked polymer–drug conjugates are known to be more stable in circulation than drug-encapsulated micelles. The SMA-THP conjugate also formed micelles and showed albumin binding capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 30 publications
(52 reference statements)
1
26
0
Order By: Relevance
“…injection by virtue of the enhanced permeability and retention (EPR) effect 1 of solid tumors, as described elsewhere [2][3][4][5][6][7]. In addition to accumulating in primary tumors, it accumulates in metastatic tumors [3][4][5][8][9][10][11]. We also showed that P-THP released active free pirarubicin more in the mildly acidic pH (near 6) of tumor tissue than in the pH of normal tissue (7.4) [2].…”
Section: Introductionsupporting
confidence: 65%
“…injection by virtue of the enhanced permeability and retention (EPR) effect 1 of solid tumors, as described elsewhere [2][3][4][5][6][7]. In addition to accumulating in primary tumors, it accumulates in metastatic tumors [3][4][5][8][9][10][11]. We also showed that P-THP released active free pirarubicin more in the mildly acidic pH (near 6) of tumor tissue than in the pH of normal tissue (7.4) [2].…”
Section: Introductionsupporting
confidence: 65%
“…A newly developed system of polymeric micelles formulated from polymer–drug conjugates has shown promising therapeutic efficacy in a mouse model of colon cancer with lung metastasis 202 , and in a pilot study of one patient with castration-resistant prostate cancer with lung and bone metastases 203 . Comparatively little effort has been devoted to exploiting nanotechnology to modify the premetastatic microenvironmental niche and suppress tumour growth.…”
Section: Targeting the Tme And The Premetastatic Nichementioning
confidence: 99%
“…This is a similar order of magnitude to the non-degradable, amphiphilic CCS polymer recently developed by us, which was synthesised via a combination of atom transfer radical polymerisation (ATRP) and copper-catalysed azide-alkyne cycloaddition (CuAAC) in a grafting-to-approach. 48,59,62,63 The slow intracellular uptake of the drug once liberated from these conjugate limits their anti-tumor efficacy. The attachment of pendant pyrene groups favours π-π interaction with pirarubicin affording loading capabilities of ca.…”
Section: Drug Loading Studymentioning
confidence: 99%